Composition, anti-quorum sensing and antimicrobial activity of essential oils from Lippia alba - Olivero-Verbel,Jesus (2014)
Many Gram-negative pathogens have the ability to produce N-acylhomoserine lactones (AHLs) as signal molecules for quorum sensing (QS). This cell-cell communication system allows them to coordinate gene expression and regulate virulence. Strategies to inhibit QS are promising for the control of infectious diseases or antibiotic resistant bacterial pathogens. The aim of the present study was to evaluate the anti-quorum sensing (anti-QS) and antibacterial potential of five essential oils isolated from Lippia alba on the Tn-5 mutant of Chromobacterium violaceum CV026, and on the growth of the gram-positive bacteria S. aureus ATCC 25923. The anti-QS activity was detected through the inhibition of the QS-controlled violacein pigment production by the sensor bacteria. Results showed that two essential oils from L. alba, one containing the greatest geranial:neral and the other the highest limonene:carvone concentrations, were the most effective QS inhibitors. Both oils also had small effects on cell growth. Moreover, the geranial/neral chemotype oil also produced the maximum zone of growth inhibition against S. aureus ATCC 25923. These data suggest essential oils from L. alba have promising properties as QS modulators, and present antibacterial activity on S. aureus.